Deep Learning-Based Identification of Echocardiographic Abnormalities From Electrocardiograms - Goro Fujiki, MD; Satoshi Kodera, MD, PhD; Naoto Setoguchi, MD; Kengo Tanabe, MD, PhD; Kotaro Miyaji, MD, PhD; Shunichi Kushida, MD, PhD; Mike Saji, MD, PhD; Mamoru Nanasato, MD, PhD; Hisataka Maki, MD, PhD; Hideo Fujita, MD, PhD; Nahoko Kato, MD, PhD; Hiroyuki Watanabe, MD, PhD; et al. (JACC: Asia)
Background: Heart failure should be diagnosed as early as possible. Although deep learning models can predict one or more echocardiographic findings from electrocardiograms (ECGs), such analyses are not comprehensive. Objectives: This study aimed to develop a deep learning model for comprehensive prediction of echocardiographic findings from ECGs. Methods: We obtained 229,439 paired ECG and echocardiography data sets from 8 centers. Six centers contributed to model development and 2 to external validation. We identified 12 echocardiographic findings related to left-sided cardiac abnormalities, valvular heart diseases, and right-sided cardiac abnormalities. These findings were predicted using convolutional neural networks, and a composite label was analyzed using logistic regression. A positive composite label indicated positivity in any of the 12 findings. Results: For the composite findings label, the area under the receiver-operating characteristic curve was 0.80 (95% CI: 0.80-0.81) on hold-out validation and 0.78 (95% CI: 0.78-0.79) on external validation. The composite findings label applying logistic regression had an area under the receiver-operating characteristic curve of 0.80 (95% CI: 0.80-0.81) with accuracy of 73.8% (95% CI: 73.2-74.4), sensitivity of 81.1% (95% CI: 80.5-81.8), and specificity of 60.7% (95% CI: 59.6-61.8). Conclusions: We have developed convolutional neural network models that predict a wide range of echocardiographic findings, including left-sided cardiac abnormalities, valvular heart diseases, and right-sided cardiac abnormalities from ECGs and created a model to predict a composite findings label by logistic regression analysis. This model has potential to serve as an adjunct for early diagnosis and treatment of previously undetected cardiac disease.